Does Rebound Tonometry Probe Misalignment Modify Intraocular Pressure Measurements in Human Eyes? - Ian G. Beasley; Deborah S. Laughton; Benjamin J. Coldrick; Thomas E. Drew; Marium Sallah; Leon N. Davies (Journal of Ophthalmology)
Purpose. To examine the influence of positional misalignments on intraocular pressure (IOP) measurement with a rebound tonometer. Methods. Using the iCare rebound tonometer, IOP readings were taken from the right eye of 36 healthy subjects at the central corneal apex (CC) and compared to IOP measures using the Goldmann applanation tonometer (GAT). Using a bespoke rig, iCare IOP readings were also taken 2 mm laterally from CC, both nasally and temporally, along with angular deviations of 5 and 10 degrees, both nasally and temporally to the visual axis. Results. Mean IOP ± SD, as measured by GAT, was 14.7±2.5 mmHg versus iCare tonometer readings of 17.4±3.6 mmHg at CC, representing an iCare IOP overestimation of 2.7±2.8 mmHg (P<0.001), which increased at higher average IOPs. IOP at CC using the iCare tonometer was not significantly different to values at lateral displacements. IOP was marginally underestimated with angular deviation of the probe but only reaching significance at 10 degrees nasally. Conclusions. As shown previously, the iCare tonometer overestimates IOP compared to GAT. However, IOP measurement in normal, healthy subjects using the iCare rebound tonometer appears insensitive to misalignments. An IOP underestimation of <1 mmHg with the probe deviated 10 degrees nasally reached statistical but not clinical significance levels.